Cocaine-mediated circadian reprogramming in the striatum through dopamine D2R and PPARγ activation - Karen Brami-Cherrier (Nature Portfolio, 2020)
Drugs of abuse have been shown to perturb circadian rhythms. Here, the authors show in mice that cocaine exposure modulates circadian gene expression in the striatum through a previously unappreciated pathway that involves dopamine D2 receptors and the nuclear receptor PPARγ.